Penerapan Strategi Pembelajaran Aplikasi Zoom Collaboration dalam Meningkatkan Motivasi Belajar Siswa di Masa Pandemi Covid-19 - Dewi, Almi Nur Mala; Azwar, Beni; Yanuarti, Eka (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the application of the zoom collaboration application learning strategy in increasing student learning motivation in the subjects of Islamic Religious Education during the Covid-19 pandemic. This research is quasi-experimental (Quasy Experiment), with a pretest and posttest control group research design. The sample in this study were 28 students from class X MA Miftahul Jannah. The results of the study, the application of the Zoom Collaboration application learning strategy can improve student learning outcomes and understanding of the subject of Islamic Religious Education, in cycle I and cycle II significantly, namely at 47.50 and 72.14. In addition, the zoom collaboration application learning strategy can increase student learning motivation seen from the positive increase in the results of the initial and final questionnaires by 320 points to 467 points. In conclusion, the application of the Zoom Collaboration application learning strategy is effective in improving learning outcomes, understanding and student motivation in Islamic Religious Education subjects during the Covid 19 pandemic in class X MA Miftahul Jannah. Keywords: Zoom collaboration Application, Learning Motivation, Learning Outcomes, PAI Learning